Impact of high- and low-glycemic index diets on salivary insulin and cortisol: a scoping review - Fairuz, Anargya Alfa; Tjahajawati, Sri; Rafisa, Anggun (Faculty of Dentistry Universitas Padjadjaran, 2025)
Introduction: Saliva is a complex biological fluid secreted by the body and has components that act as biomarkers indicating various health conditions. Recent studies have shown inconsistencies between the glycemic index (GI) and components in saliva, especially insulin and cortisol. This study aims to map the relationship between glycemic index diets (high and low) and salivary insulin and cortisol levels. Method: This scoping review followed the Joanna Briggs Institute guidelines, with searches conducted in PubMed, ScienceDirect, Google Scholar, and Scopus databases from 2012 to 2023. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Review (PRISMA-ScR) framework was used for study identification and article writing. Results: Nine articles met the inclusion criteria, and data were extracted from each article. This scoping review involved 282 healthy individuals (141 males and 141 females) aged 9–55 years, with only one study focused on the pediatric population. One study examined cortisol and insulin levels together; while the remaining eight studies investigated them separately. Conclusions: This review highlights a complex interplay between GI diets and salivary biomarkers, particularly insulin and cortisol. While high-GI diets may influence salivary insulin, their impact on cortisol appears less consistent. These findings suggest that salivary biomarkers could serve as non-invasive tools for monitoring dietary impacts on metabolic and stress-related health. Further research is needed to address limitations such as population diversity, dietary standardization, and confounding factors to enhance clinical and dietary applications.